CONFORMACIÓN DE ALIANZAS ESTRATÉGICAS BANCOS - EMPRESA Y SU IMPACTO PARA UN SISTEMA FINANCIERO INCLUSIVO - López Mas, Julio (2009)
The nature of the correspondent banking, in the particular case of Banco de Crédito del Perú (BCP) through its financial product BCP Agent, allows interconnection between enterprises (including SMEs) and implementation on behalf of BCP (entity that this channel promotes care) financial transactions that under other circumstances would be expensive to perform. So are some impacts on stakeholders: the companies and / or individuals as agents. Among the impacts, economic and noneconomic from this strategy, we have depth in the banking system to allow for minor operations closer to the population, and from a financial perspective there is a positioning of the BCP as an institution more inclusive the banking system.